Simulation Analysis on Drainage Consolidation Characteristics of Hydraulic Fill Soft Soil. Issue 1 (March 2021) - Yu, Shengyou; Quan, Xiaojuan; You, Kaikai; Ding, Jihui; Gan, Yu
Abstract: Based on the treatment of dredger fill soft soil foundation in Eastern Shantou, Guangdong Province, consolidation theory and numerical simulation based on composite consolidation coefficient are used to study the consolidation characteristics of dredger fill soft soil, and the results are compared with the field monitoring results. The calculation results show that the theoretical consolidation degree of the site is 93.4%, which is basically consistent with the final consolidation degree of field monitoring. In the first two stages of surcharge loading, field monitoring is faster than theoretical calculation. The field monitoring value of the final settlement is 1342 mm, which is about 10% less than the theoretical value. The final average consolidation degree of the two models is 97.9%, which is 4.7% more than the field monitoring value. The results show that the pore water pressure law is obvious, the dissipation rate is about 16% higher than the field monitoring value, and the consolidation effect is more obvious. The numerical simulation of the composite coefficient model has certain applicability and can be used to guide the design and construction of similar projects.